Exploring the purpose and stages of patient and public involvement and engagement (PPIE) in audiology research: a case study approach - Helen Pryce; Nisha Dhanda; Jean Straus (Research Involvement and Engagement)
Abstract Background Patient and Public Involvement and Engagement (PPIE) has become an integral component of contemporary audiology research. It aims to capture diverse views and experiences, essential for evaluating the long-term impact of technological advancements and care models on individuals. Traditional inclusion methods, such as focus groups, may exclude individuals with additional needs or communication difficulties, necessitating the development of more inclusive approaches. Methods This study explores PPIE’s purpose and stages in two recent audiology studies, adhering to the Guidance for Reporting Involvement of Patients and the Public (GRIPP2) criteria. The authors describe their attempts to optimise participation by PPIE volunteers in two studies. The methods sought to engage volunteer PPIE contributors who might otherwise have not known about or contributed views of research methods. Specifically, our novel methods for engagement meant reaching out deliberately to marginalised communities and using individual, relationship building approaches, rather than relying on previously described focus group style meetings. Flexible engagement methods were developed to include marginalised communities with lower levels of research engagement. In the first study, the Hearing Loss and Patient Reported Experience Study (HeLP) developed the first Patient-Reported Experience Measure (PREM) in audiology. The study involved creating a conceptual framework, developing a prototype questionnaire, and validating it through test-retest procedures. The second study conducted an ethnographic analysis of adults with dementia and hearing loss in care homes, employing environmental audits, ethnographic observations, and semi-structured interviews. Results The HeLP study successfully developed a culturally meaningful and accessible PREM, capturing the experiences of individuals with hearing loss, including those from South Asian communities. PPIE contributors highlighted the need for non-judgmental, empathetic approaches and culturally sensitive language. The PPIE component of the ethnographic study emphasises the importance of creating appropriate communication environments and implementing tailored inclusion strategies to address barriers faced by PPIE contributors in their participation. Conclusions The findings stress the necessity of inclusive PPIE methods in audiology research. Building meaningful relationships with PPIE contributors ensures a wide range of perspectives, informing research design and conduct. The study highlights the challenges of traditional focus groups and the benefits of flexible, personalised engagement methods. By prioritising relationship building and nuanced conversations, researchers can develop interventions that better align with users’ needs, preferences, and lifestyles. This approach contributes to the growing body of literature advocating for more inclusive and representative PPIE practices in health research, ultimately enhancing the relevance and impact of audiology studies.